Application of a large-screen immersive visualisation system to demonstrate sustainable mining practices principles - Stothard, Phillip; Laurence, D. (Maney Publishing, 2014)
Can large-screen visualisation and simulation technology be utilised to depict sustainable mining practices? The system described here provides an opportunity to experience a mine site and the surrounding area via visualisation and simulation. The system presents sustainable mining concepts that must be managed at a mine site surrounded by a national park. The system includes historic and current data and perspectives from mine site, environmental and local personnel. All information must be assessed against an original environmental impact statement and conclusions be drawn upon how the mine has developed. Knowledge gained is transferred to a new site, and issues must be resolved to the satisfaction of all stakeholders. The paper summarises the system and reports outcomes of a trial deployment. The results are encouraging, and the system may prove to be a useful tool for community engagement and mine planning on future projects.